2019
DOI: 10.1371/journal.pone.0218668
|View full text |Cite
|
Sign up to set email alerts
|

Etiology, characteristics, and outcomes of community-onset necrotizing fasciitis in Korea: A multicenter study

Abstract: Background Necrotizing fasciitis (NF) is a serious skin and soft tissue infection causing high mortality. Investigating region specific epidemiologic factors associated with NF is important for establishing appropriate treatment strategies. This multicenter study was done to provide an update of the microbial etiology, clinical characteristics, and outcomes of NF in Korea. Materials and methods A retrospective cohort of adult patients with NF was established using patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…Most commonly, it is a polymicrobial infection caused by aerobic and anaerobic bacteria. Kim et al reported that 73.9% had one or more identifiable pathogens [ 23 ]. Bair et al stated that a single pathogen was found as the infectious agent in 60.4% and multiple pathogens in 19.8% in their study [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most commonly, it is a polymicrobial infection caused by aerobic and anaerobic bacteria. Kim et al reported that 73.9% had one or more identifiable pathogens [ 23 ]. Bair et al stated that a single pathogen was found as the infectious agent in 60.4% and multiple pathogens in 19.8% in their study [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some literature data reported that the prevalence of NF is about 1-4 cases per 100.000 populations; men are commonly affected, with a male-to-female ratio of 3:1 [1]. However, there are studies showing different results, so, male to female ratio by Eke et al is approximately 10:1 [5], and in the study of Kim et al, men accounted for 67.1% [6].…”
Section: Discussionmentioning
confidence: 93%
“…Similar results were reported by multicenter studies in South Korea, with approximately 20% mortality in GAS-NF cases compared to 58% of mortality in K. pneumoniae NF. Moreover, patients with Gram-negative infections were more likely to have chronic alcoholism, intensive care admission, and septic shock [16]. Furthermore, another study reported that NF patients with DM had more than a seven-fold increase in mortality if K. pneumoniae was present in blood cultures and wounds [8,16].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with Gram-negative infections were more likely to have chronic alcoholism, intensive care admission, and septic shock [16]. Furthermore, another study reported that NF patients with DM had more than a seven-fold increase in mortality if K. pneumoniae was present in blood cultures and wounds [8,16]. Many cases of K. pneumoniae infection have mixed pathogens, which are more likely to develop bacteremia and distant abscesses.…”
Section: Discussionmentioning
confidence: 99%